2020
DOI: 10.1080/20016689.2020.1717030
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the global measurement of willingness to pay in health

Abstract: Objective: To understand the different methodologies used to elicit willingness to pay for health and the value of a statistical life year through surveys. Methodology: A systematic review of the literature was undertaken to identify studies using surveys to estimate either willingness to pay for health or the value of a statistical life year. Each study was reviewed and the study setting, sample size, sample description, survey administration (online or face to face), survey methodology, and results were extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 41 publications
0
84
0
3
Order By: Relevance
“…No strategies using remdesivir monotherapy were favoured and in most cases were less effective and more costly than other strategies in the base-case. Multivariate analysis showed that remdesivir for moderate and dexamethasone for severe infections remained the preferred choice when willingness to pay thresholds are over $37,500 USD, which is a relevant threshold in countries such as Canada, Ireland, Australia, Spain and the United Kingdom 16 .…”
Section: Discussionmentioning
confidence: 99%
“…No strategies using remdesivir monotherapy were favoured and in most cases were less effective and more costly than other strategies in the base-case. Multivariate analysis showed that remdesivir for moderate and dexamethasone for severe infections remained the preferred choice when willingness to pay thresholds are over $37,500 USD, which is a relevant threshold in countries such as Canada, Ireland, Australia, Spain and the United Kingdom 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Country-specific willingness-to-pay thresholds are difficult to determine from available evidence as various methodologies exist. 18 The World Health Organization CHOICE (CHOosing Interventions that are Cost-Effective) project has recommended thresholds of 1–3 times the gross domestic product (GDP) per capita, with those interventions meeting the <1 GDP threshold considered highly cost-effective. 19 Therefore, we examined the cost-effectiveness at WTP thresholds of near 1 GDP (~$40,000 in UAE) and 3 GDP per capita (~$120,000 in UAE).…”
Section: Resultsmentioning
confidence: 99%
“…This threshold is equivalent to 1 GDP per capita in Colombia. The Colombian methodological guide for economic evaluations established this threshold to consider a technology highly cost-effective following the recommendations of the World Health Organization [ 28 , 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%